Serafín Estébanez Calderón, "El Solitario", periodista taurino. - Fórneas, Celia (Estudios sobre el Mensaje Periodístico, 2000)
This is a first analysis of Serafín Estébanez Calderón, El Solitario (1799-1867) bullfighting journalism. He was a romantic poet and writer of the famous "Escenas Andaluzas" who developped other several jobs, both in the military and the civil fields. El Solitario offers us a well-documented biography prepared by his nephew, Antonio Cánovas del Castillo (King Alfonso XII´s first chief of Government); biography that was rewritten and updated by Jorge Campos in 1955, for his Vida y obra de D. Serafín Estébanez Calderón, 167 María Celia Forneas Serafín Estébanez Calderón, "El Solitario", periodista taurino who also identified Estébanez Calderón´s bull-fighting works through a letter from Estébanez Calderón to his friend Pascual Gayancos inserted in El Solitario y su tiempo written by Cánovas del Castillo.